Remote teaching for Specialized Educational Assistance students (Research, Society and Development, 2020)
To contain the contagion by the Covid-19 pandemic, one of the first measures of social distancing was the suspension of face-to-face classes. The alternative that became viable in the current conjuncture was remote education.  This work aims to outline an overview of how the teachers of specialized educational care (SEC) of the municipal school system of Uruguaiana/RS have been developing this service in Remote Education. To this end, a questionnaire was developed applied to 09 SEC teachers in the municipality. The qualitative analysis of the questionnaire was based on 7 categories that include: professional academic training, continuing education, understanding about remote teaching, diversity of special needs met, number of services, resources employed in remote mediation and the effectiveness of the service in promoting learning through remote teaching. As results we obtain that the teachers surveyed have adequate training, as well as have carried out numerous training courses via distance learning. According to teachers there are between 11 and 24 students in each school requiring care with the most varied disabilities. The activities of the SEC have been carried out remotely through digital/print technology resources and the help of the students' families. The effectiveness of this care depends on different factors such as: the type of special need, the student's ability to interact with digital/printed media and family commitment.  Inclusive education in remote education has been partially occurring mainly because it is difficult to include the school environment in a remote way.